Evaluation of specialty soy protein sources on nursery pig performance - Jordan, Kyle E.; Goncalves, Marcio Antonio Dornelles; Tokach, Michael D.; Dritz, Steven S.; Goodband, Robert D.; DeRouchey, Joel M.; Woodworth, Jason C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A 35-d growth trial was conducted to evaluate the effects of a new soy protein source, Nutrivance (TechMix, Stewart, MN), on nursery pig growth performance. Nutrivance is a modified soy protein produced via a proprietary process combining extraction and enzymatic treatment of soybeans. Pigs (n = 1,188, PIC 337 × 1050; initially 9.8 lb BW) were weaned at 21 d of age and allotted by weight to pens with 27 pigs per pen. Pigs were fed a common diet for 15 d before the start of the study. Pens of pigs (13.5 lb BW) were then allotted to 1 of 4 dietary treatments fed for 14 d followed by a common diet fed for 21 d. The 4 experimental treatments were a corn-soybean meal–based control diet, or a corn-soybean meal–based diet with either 8% Nutrivance, 8.65% HP-300 (Hamlet Protein, Findlay, OH), or 6.85% Soycomil P (SPC; Archer Daniels Midland Co., Decatur, IL). The diets were formulated to the same standardized ileal digestible lysine level with specialty soy protein products replacing a portion of soybean meal in the control diet to form the experimental treatments. From d 0 to 14, there were no differences in ADG or F/G; however, pigs fed the diets containing Nutrivance or HP-300 had decreased ADFI (P < 0.02) compared with those fed the control diet, with pigs fed diets containing SPC intermediate. From d 14 to 35 when a common diet was fed, pigs previously fed the diet with the HP-300 had lower ADFI (P < 0.03) compared with pigs fed the control diet, with pigs previously fed diets containing Nutrivance or SPC intermediate. From d 0 to 35, pigs fed diets containing Nutrivance or HP-300 had decreased ADG and ADFI (P < 0.02) compared with pigs fed the control diet, with pigs fed diets containing SPC intermediate. Final weight (d 35) was greatest (P < 0.04) for pigs fed the control diet and lowest for pigs fed the diet with Nutrivance, and pigs fed the diets with HP-300 or SPC were intermediate. In conclusion, differences exist between alternative specialty soy protein sources, but, the corn-soybean meal control diet elicited the greatest growth performance in this study.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Growth performance; Nursery pig; Soy protein sources